A study on the high-pressure synthesis and properties of praseodymium-substituted R(2)Ba(4)Cu(7)O(14+delta) (R=Nd, Eu, Tm) cuprates - Kao, FS; Chen, TM (My University, 1996)
The formation of phases in the (R(1-x)Pr(x))(2)Ba4Cu7O?(14+delta (R = Nd, Eu, Tm; Pr-doped R247 phases) system with x = 0 - 0.5 was investigated. Samples of the above three series were synthesized at 980 degrees C at 25 bar O-2, followed by annealing at 300 degrees C under 130 bar O-2 for 30 hours. Oxygen content of the samples has been determined by iodometric titration. X-ray diffraction indicated that nearly single-phased samples were obtained with err < 0.4, 0.5 and 0.5 for R = Nd, Eu and Tm, respectively, and the cell dimension of the Pr-doped R247 phases was found to expand steadily with increasing Pr content. Field-cooled temperature-dependent magnetization measurements showed that T-c of the Pr-doped R247 decreased with increasing Pr content. We have compared the dT(c)/dx for the three series with R = Nd, Eu and Tm with that for R = Y as a function of size of R(3+) ions and the results are discussed. In addition, the field-dependent magnetization studies at 5 K for a series of (Eu1-xPrx)(2)Ba4Cu7O14+delta samples with x = 0, 0.2, and 0.4 are also reported.